Humanization of the hospital: participatory construction of knowledge and practices on care and ambience* - Salvati, Caroline de Oliveira; Gomes, Carine Alves; Haeffner, Leris Salete Bonfanti; Marchiori, Mara Regina Caino Teixeira; Silveira, Rosemary Silva da; Backes, Dirce Stein (Revista da Escola de Enfermagem da USP, 2021)
Objective: To identify and implement care and ambience strategies, with a view to hospital humanization. Method: Action-research study, whose investigation process occurred between January and March 2019, with the participation of employees in strategic functions of a medium-sized hospital, through a focus group and strategic focal analysis. The implementation of care and ambience strategies started in May 2019 and remains in progress, with the responsible and multiplying participation of professionals and patients. Results: 18 employees participated in the study. It was found that investigative processes accompanied by practical interventions, especially those related to the promotion of interactive, inclusive, care spaces and the creation of a ludic, attractive and interactive environment favor multi-professional actions, mobilize innovative knowledge and practices, and contribute to the (re)signification of the being and doing of the health professional. Conclusion: Care and ambience, with a view to hospital humanization, include the implementation of strategies designed with the responsible and multiplying participation of all actors (professionals and users) of the hospital. It is important that, in this process, everyone feels they are protagonists of new ways of being, living and doing in health.